2020
DOI: 10.3390/min10110973
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Iron from Copper Slag Using Coal-Based Direct Reduction: Reduction Characteristics and Kinetics

Abstract: The Fe3O4 and Fe2SiO4 in copper slag were successfully reduced to metallic iron by coal-based direct reduction. Under the best reduction conditions of 1300 °C reduction temperature, 30 min reduction time, 35 wt.% coal dosage, and 20 wt.% CaO dosage (0.75 binary basicity), the Fe grade of obtained iron concentration achieved 91.55%, and the Fe recovery was 98.13%. The kinetic studies on reduction indicated that the reduction of copper slag was controlled by the interfacial reaction and carbon gasification at 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 43 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…In previous studies, the initial characterization of smelter slag was followed by the proposal of a process route to utilize the slag. The slag can be characterized using Xray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy with energy-dispersive spectrometry (SEM-EDS), and light optical microscopy (LOM) in transmitted and reflected light [45][46][47]. Previous studies have indicated that copper slag behaves differently when subjected to different temperatures, thus exhibiting different properties [42,48].…”
Section: Uses Of Metallurgical Slagmentioning
confidence: 99%
“…In previous studies, the initial characterization of smelter slag was followed by the proposal of a process route to utilize the slag. The slag can be characterized using Xray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy with energy-dispersive spectrometry (SEM-EDS), and light optical microscopy (LOM) in transmitted and reflected light [45][46][47]. Previous studies have indicated that copper slag behaves differently when subjected to different temperatures, thus exhibiting different properties [42,48].…”
Section: Uses Of Metallurgical Slagmentioning
confidence: 99%
“…Further slag processing or their direct use depends on the contents of valuable metal compounds and the contents of toxic metals, which are environmentally unfriendly and cannot be safely stored. In slags derived from various technological processes of copper production, the fractions of this chemical element widely differ, ranging from 0.5 wt% Cu to 16 wt% Cu [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Moreover, these slags contain heavy metals (e.g., lead, zinc, arsenic, chromium, mercury), and their compounds may pose a major hazard when released into the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a significant proportion of the sulfides are locked in the fayalite phase, requiring costly fine grinding to liberate the sulfides for effective recovery by flotation [8,10,11]. A common pyrometallurgical route in slag cleaning is the carbothermal reduction method at high temperatures of around 1400 • C using a DC arc furnace; however, high energy consumptions remain an associated challenge [9,12]. A combined pyro-hydrometallurgical method of roasting with subsequent leaching is a commonly studied method in slag treatment [8,13,14].…”
Section: Introductionmentioning
confidence: 99%